Aristotle on the Cause of Unity: The Argument of Metaphysics H.3–6 - Pfeiffer, Christian (Phronesis, 2024)
I argue that Metaphysics H.6 is not an isolated chapter but the conclusion of an argument begun in H.3. This view will provide further and better arguments for the following view about long-standing interpretative debates: first, Aristotle provides a substantive account of the unity of the composite substance (although he also briefly addresses the unity of the form); second, neither Aristotle’s conception of matter nor his account of form changes between H.1–5 and H.6; and third, H does not rely on and is not completed by book Θ in any significant way.